HASIL PENERAPAN METODE LATIHAN SET SYSTEM DENGAN POLA PROGRESIF PADA BENTUK LATIHAN BAND RESISTED BROAD JUMP DAN 45 DEGREES LEG PRESS TERHADAP PENINGKATAN POWER OTOT TUNGKAI PADA CABANG OLAHRAGA BOLA VOLI - Dhiva Ghufron Nurzabin, - (2022)
Leg power is strongly tied to a player's ability to perform high leaps due to the strength of their leg muscles. Possessing strong leg power is ideal for a volleyball player and is one of their requirements. To develop muscular leg power in volleyball, this study will evaluate the effects of applying the set system with progressive pattern training method through band-resisted broad jumps and 45-degree leg presses. An experimental approach using a two-group pre-test/post-test design was used in this study. Using a complete sampling technique, this study examined 20 athletes from the Sekelimus PBV team. Two groups, the experimental class, were given a pre- test as part of the data collection technique. Following the therapy (treatment) administration in the form of 45-degree leg press and band-resisted broad jump exercises for group B and group A, respectively, the Vertical Jump Test was employed for the final and post-test. The two methods of data processing used were descriptive statistical analysis and comparative test analysis-these two types of exercise both impact the development of leg muscle power. However, resistance band training has an average rise in leg muscle power of 99.80%. While the sample employing the Leg Press method's average value of leg muscle power showed a change of 35.90% from the starting value (posttest). Therefore, it can be stated that employing resistance bands as a form of exercise has a more notable impact on improving muscular leg power in volleyball. Keyword: Leg muscle power, Band Resisted Broad Jump, 45 Degree Leg Press Volleyball